Identification of Subsurface Structures of Accretion Area Using HVSR Method: A Case Study of Bengkulu City - Apriana, Agnes; Azhari, M. Fikri; Yuliza, Elfi; Refrizon, Refrizon (Faculty of Science and Technology Universitas Islam Negeri Ar-Raniry, 2025)
Abstract: Bengkulu City, located in a tectonically active accretion zone, was selected as the study area due to its high susceptibility to seismic hazards The Horizontal to Vertical Spectral Ratio (HVSR) method based on microtremor data is an effective non-invasive technique to determine the dominant frequency (fo ), amplification factor (Ao ), and shear wave velocity profile (Vs ). This study aims to identify subsurface structures in the accretion area of Bengkulu City by analyzing microtremor data using the HVSR method. Data acquisition was conducted at 45 measurement points, recorded using a PASI Mod Gemini 2 Sn 1405 Seismometer. Data analysis utilized the Python version 3.7.0 computing platform and the Terraware-HV to derive HV curves describing the fo and Ao. The values of fo and Ao were used to calculate the seismic susceptibility index (Kg). Furthermore, the inversion of HVSR curves was conducted to obtain the Vs. The results showed that fo 0.90-2.10 Hz, Ao 2.08-5.49, Kg 4.36-21.68, and Vs30 were identified as type D (180≤ Vs < 360), which indicates that the subsurface rock consists of a stiff soil layer. Furthermore, Vs the inversion of the HVSR curve shows that vertically, the subsurface structure of the study area consists of several layers, namely soft soil, stiff soil, very dense soil, and soft rock. The 3D model of the Vs distribution confirms that the study area, consistent with its identity as an accretion zone, is predominantly composed of alluvial deposits, including layers of sand and clay. Abstrak: Kota Bengkulu, yang terletak di zona akresi yang aktif secara tektonik, dipilih sebagai area penelitian karena kerentanannya yang tinggi terhadap bahaya seismik. Metode Horizontal to Vertical Spectral Ratio (HVSR) berbasis data mikrotremor merupakan teknik non-invasif yang efektif untuk menentukan frekuensi dominan (fo), faktor amplifikasi (Ao), serta profil kecepatan gelombang geser (Vs). Penelitian ini bertujuan untuk mengidentifikasi struktur bawah permukaan daerah akresi Kota Bengkulu dengan menganalisis data mikrotremor menggunakan metode HVSR. Akuisisi data dilakukan pada 45 titik pengukuran menggunakan seismometer PASI Mod Gemini 2 Sn 1405. Analisis data memanfaatkan platform komputasi Python versi 3.7.0, dan Terraware-HV untuk memperoleh kurva HV yang menggambarkan fo dan Ao. Nilai fo dan Ao digunakan untuk menghitung indeks kerentanan seismik (Kg). Selanjutnya, dilakukan inversi kurva HVSR untuk mendapatkan profil Vs. Hasil penelitian menunjukkan fo 0,90-2,10 Hz, Ao 2,08-5,49, Kg 4,36-21,68, dan Vs30 yang teridentifikasi adalah tipe D (180≤ Vs < 360), yang menunjukkan bahwa batuan bawah permukaan terdiri dari lapisan stiff soil. Selanjutnya, Vs berdasarkan inversi kurva HVSR menunjukkan bahwa secara vertikal, struktur bawah permukaan daerah penelitian terdiri dari beberapa lapisan, yaitu soft soil, stiff soil, very dense soil, dan soft rock. Model 3D distribusi Vs menegaskan bahwa area studi, sesuai dengan identitasnya sebagai zona akresi, sebagian besar terdiri dari endapan aluvial, termasuk lapisan pasir dan tanah liat